1992
DOI: 10.1017/s000748530005166x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the emergence of Hypothenemus hampei (Coleoptera: Scolytidae) from coffee berries

Abstract: Emergence of coffee berry borer, Hypothenemus hampei (Ferrari), from infested coffee berries (Coffea arabica) was studied in the laboratory under controlled temperature and relative humidity (RH) regimes. Low humidities (<60% RH, 25°C) provoked rapid evacuation of adults. Emergence was at a minimum at 90% RH. A steady increase in emergence occurred at values from 90 to 100% RH. Emergence was low below 20°C (90 and 100% RH) and increased markedly between 20 and 25°C. There was no significant increase in emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 5 publications
3
48
1
6
Order By: Relevance
“…Klein-Koch et al (1988) found that in a high rainfall zone of Ecuador (3300 mm year -1 ) more than 80% of bored berries fallen to the ground were rotted and with a very low population of borers; ripe and overripe berries were the most affected. Emergence of borers from infested berries at high humidities was also reported by Baker et al (1992b) to avoid problems of pathogens such as B. bassiana or to look for more suitable berries for reproduction. According to this it is feasible also to think that extreme climatic conditions or colonizing organisms could kill and/or remove borers from the infested berries.…”
Section: Resultsmentioning
confidence: 92%
“…Klein-Koch et al (1988) found that in a high rainfall zone of Ecuador (3300 mm year -1 ) more than 80% of bored berries fallen to the ground were rotted and with a very low population of borers; ripe and overripe berries were the most affected. Emergence of borers from infested berries at high humidities was also reported by Baker et al (1992b) to avoid problems of pathogens such as B. bassiana or to look for more suitable berries for reproduction. According to this it is feasible also to think that extreme climatic conditions or colonizing organisms could kill and/or remove borers from the infested berries.…”
Section: Resultsmentioning
confidence: 92%
“…6). Rainfall triggers colonization flights of H. hampei females [63][64]; an effect that is enhanced by high temperatures in the plantation [64].…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic and intrinsic factors are known to motivate H. hampei females to abandon residual coffee fruits and colonize fresh fruits during the period between harvests (Baker et al 1992b, Mathieu et al 1997, Barrera et al 2006. Intrinsic, or physiological, factors include fecundity, nulliparousness, ßight muscle condition, and apparently, the borer diapause stage that occurs during the interharvest period (Ticheler 1961, Mansingh 1991, Mathieu et al 1997, Barrera et al 2006.…”
Section: Discussionmentioning
confidence: 99%